Antifungal Active Fraction of Peria Pantai(Colubrina Asiatica (L.) Brong) Leaf Against Fluconazole-Resistance Candida Albicans - Irma, Sari; Risa, Nursanty; Y, Yulidar (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: A novel antifungal needs to be found to overcome fungal resistance to antifungal drugs. Medicinal plants contain biologically active compounds as antifungal agents. Peria Pantai (Colubrinaasiatica L. Brong) has been used as a folk medicine by the Acehnese community to treat skin disease. This research aim was to evaluate antifungal activity of C. asiatica leaf fraction against Candidaalbicans resistant fluconazole.Methode: The extraction was accomplished consecutively as solvent multistep using n-hexane, ethyl acetate, and methanol. Phytochemical investigation has done to each extract/fraction. The antifungal activity has been evaluated by Kirby-Bauer method.Result: The result of phytochemical investigation of n-hexane fraction contains steroid compound, ethyl acetate fraction contains saponin and steroid compounds, and the methanol fraction contains flavonoid, saponin, tannin, and steroid compounds. n-Hexane and ethyl acetate fraction of Peria Pantai leaf have not shown antifungal activity, while it has been shown on methanol fraction with inhibition zone 5,6; 7,17; 8,25; and 11,4 mm at 10%, 20%, 30% and 40%concentration.